Risk factors of sepsis in premature infants - Stošić-Krajčinović Svetlana (Association of Nurses Technicians and Midwives, 2015)
Introduction: Neonatal sepsis is one of the most important causes of morbidity and mortality in preterm infants. Neonatal sepsis is defined as invasive bacterial infection that occurs in newborn children from the first to the ninetieth day of life. Hemoculture still represents the gold standard for the detection of sepsis. Blood culture may be falsely positive due to contamination of the samples. Contaminated blood cultures increase treatment costs and extend the length of stay of premature babies in hospitals. The aim of the study was to determine the incidence and risk factors of sepsis in premature infants who are being treated in the intensive care. Also to determine whether preventive medical-technical procedures will reduce the incidence of neonatal sepsis, as well as a reduction in contamination hemocultures. Materials and Methods: 239 premature infants have been analysed in whom the observed risk factors can lead to the onset neonatal sepsis. The preventive actions that could lead to a reduction of contamination in hemocultures have also been analysed. Results: The most common risk factors for sepsis is a small gestational age and body weight below 2000g. By using aseptic techniques for taking hemocultures there was a significant reduction in contamination of the same. Conclusion. Statistical analysis of the data identified the most common factors that lead to the occurrence of neonatal sepsis and proved the significance of the reduction of hemoculture contamination after the introduction of aseptic procedures and check lists.